THE CONSTRUCTIVIST APPROACH IN ISLAMIC RELIGIOUS EDUCATION: A THEORETICAL ANALYSIS AND PEDAGOGICAL IMPLICATIONS: Pendekatan Konstruktivisme dalam Pendidikan Agama Islam: Analisis Teoretis dan Implikasi Pedagogis - Raysa Rahma; Ishomuddin; Zuliana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The constructivist approach has become a learning paradigm that has received widespread attention in various educational disciplines, including Islamic Religious Education (IRE). Although there have been many empirical studies in general education, theoretical studies that analyze the relationship between constructivism and the epistemology and pedagogy of IRE in depth are still limited. This article aims to theoretically analyze the constructivist approach in the context of Islamic Religious Education and examine its pedagogical implications for the planning, implementation, and evaluation of IRP learning. This study uses the library research method with content analysis and literature synthesis from national and international journal articles published between 2016 and 2025. The results of the study show that constructivism provides a strong conceptual foundation for developing student-centered, dialogical, reflective, and contextual Islamic Religious Education learning. Its pedagogical implications include changing the role of teachers to facilitators, using active learning strategies such as problem-based learning and reflective discussions, and evaluations that assess the cognitive, affective, and reflective aspects of students. This article recommends the integration of constructivism principles into the curriculum and learning practices of Islamic Religious Education at various levels of education as an effort to enrich the integrity of religious learning.